Odpowiedzi

2010-02-16T17:41:16+01:00
A ) 6(a+2b)-3(2a-3b)=3b
b ) 4(b+3)+3(a-b)=b+12+3a
c ) 7(b+c)-3(b+2c)=7b+13c
d ) 5(a+3)+2b-3(a+b)=2a+15+5b
e ) 6(3+z)-4(2z+4)+2(8+z)=50
f ) -4(2x-7-3y)-12(-y-x)=4x+24y+28
24 3 24
Najlepsza Odpowiedź!
2010-02-16T17:42:25+01:00
A ) 6(a+2b)-3(2a-3b)= 6a+12b-6a+9b= 21b
b ) 4(b+3)+3(a-b)=4b+12+3a-3b=3a+b+12
c ) 7(b+c)-3(b+2c)=7b+7c-3b-6c=4b+c
d ) 5(a+3)+2b-3(a+b)=5a+15+2b-3a-3b=2a-b+15
e ) 6(3+z)-4(2z+4)+2(8+z)=18+6z-8z-16+16+2z=18
f ) -4(2x-7-3y)-12(-y-x)=-8x+28+12y+12y+12x=4x+24y+28
30 3 30
2010-02-16T17:46:40+01:00
A ) 6(a+2b)-3(2a-3b)=6a+12ab-6a+9b=12ab+9b=3b(4a+3)
b ) 4(b+3)+3(a-b)=4b+12+3a-3b=3a+b=12
c ) 7(b+c)-3(b+2c)=7b+7c-3b-6c=4b+c
d ) 5(a+3)+2b-3(a+b)=5a+15+2b-3a-3b=2a-b+15
e ) 6(3+z)-4(2z+4)+2(8+z)=18+6z-8z-16+16+2z=18
f ) -4(2x-7-3y)-12(-y-x)= -8x+14+12y+12y+12x=4x+24y+14
12 2 12